Experience with a six‐month regimen of Pneumocystis pneumonia prophylaxis in 122 HIV‐positive kidney transplant recipients. Issue 3 (2nd December 2020) - Mejia, Christina D.; Malat, Gregory E.; Boyle, Suzanne M.; Ranganna, Karthik; Lee, Dong Heun
Abstract: Anti‐ Pneumocystis pneumonia (PCP) prophylaxis is recommended for 3 to 6 months post‐transplant in HIV‐negative kidney transplant recipients. For HIV‐positive kidney transplant recipients, there is no definite duration of primary prophylaxis and is often prescribed life‐long. The objective of this study was to determine the incidence of PCP in HIV‐positive recipients who received 6 months of prophylaxis with trimethoprim‐sulfamethoxazole or an alternative agent. One hundred and twenty‐two HIV‐positive recipients received a kidney transplant from 2001 to 2017 at Hahnemann University Hospital. Most patients received induction immunosuppression with an IL‐2 receptor antagonist, with or without intravenous immunoglobulin. Only one patient received anti‐thymocyte globulin. Maintenance immunosuppression included a calcineurin‐inhibitor (tacrolimus or cyclosporine), an antiproliferative agent (mycophenolate or sirolimus), and prednisone. Mean CD4 cell count was 461 ± 127 cells/uL prior to transplant and 463 ± 229 cells/μL at 6 to 12 months after transplant. None of the recipients developed PCP after a median follow‐up of 2.88 years (IQR 1.16‐4.87). Based on our observation, a 6‐month regimen of PCP prophylaxis may be sufficient among HIV‐positive recipients, similar to those without HIV infection.